Nudging When the Descriptive Norm Is Low: Evidence from a Carbon Offsetting Field Experiment - Stefano Carattini; Julia Blasch (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Nudges and behavioral interventions have become a popular tool to stimulate prosocial behavior. Little is known, however, on how to design effective social interventions in contexts in which the descriptive norm is low, i.e. when a desirable behavior is only practiced by a minority within the respective reference group. Bringing climate-friendly behaviors from nonnormative to normative is, however, crucial to tackle the climate crisis. We take up this challenge, devise a new strategy for social interventions, and test it with an especially sophisticated target group. In particular, we implemented a field experiment at two subsequent conferences in environmental economics, with which we examine the conference participants' proclivity to offset their carbon emissions as part of the standard registration process. We introduced two randomized treatment conditions, one relying on social norms and one on social identity, to be compared with a neutral control group. The social norm treatment leverages past contributions to voluntary carbon emissions at those conferences. The social identity treatment primes participants' social identity as environmental economists. We provide two main insights. First, if properly adjusted to the context, interventions leveraging social norms can be effective in changing behavior also when the descriptive norm is low and when the target group is composed of experts, if targeted individuals feel socially close to the referenced peer group. Second, the effectiveness of such interventions increases as individuals are exposed to multiple "doses" of treatment, although with decreasing marginal returns. Hence, our paper provides novel insights to policymakers and practitioners on the use of social interventions when the descriptive norm is low as well as on the ability of nudges to affect experts.
Keywords: A11; C93; D12; D91; H23; H41; Q54; 330; carbon offsets; social norms; social identity; nudge; field experiment